Nitro-fatty acids suppress ischemic ventricular arrhythmias by preserving calcium homeostasis - Mollenhauer, Martin; Dewenter, Matthias (Scientific reports, 2020)
Nitro-fatty acids are electrophilic anti-inflammatory mediators which are generated during myocardial ischemic injury. Whether these species exert anti-arrhythmic effects in the acute phase of myocardial ischemia has not been investigated so far. Herein, we demonstrate that pretreatment of mice with 9- and 10-nitro-octadec-9-enoic acid (nitro-oleic acid, NO2-OA) significantly reduced the susceptibility to develop acute ventricular tachycardia (VT). Accordingly, epicardial mapping revealed a markedly enhanced homogeneity in ventricular conduction. NO2-OA treatment of isolated cardiomyocytes lowered the number of spontaneous contractions upon adrenergic isoproterenol stimulation and nearly abolished ryanodine receptor type 2 (RyR2)-dependent sarcoplasmic Ca2+ leak. NO2-OA also significantly reduced RyR2-phosphorylation by inhibition of increased CaMKII activity. Thus, NO2-OA might be a novel pharmacological option for the prevention of VT development.